Treatment Results of Patients With Lupus Nephritis: A Single Center’s Experience - Cahit Gunes; Mustafa Keles; Abdullah Uyanik; Ramazan Cetinkaya; Refik Ali Sari (Eurasian Journal of Medicine, 2010)
Objective: Lupus nephritis (LN) is a type of organ involvement of systemic lupus erythematosus (SLE) that leads to disease-related morbidity and mortality. Lack of good treatments for LN continues to be problematic. Many different treatment protocols are applied in treatment centers. Not every treatment protocol is successful. Moreover, patients who reached remission may present with exacerbations. In this study, we aimed to evaluate the treatment results of our patients and investigate their remission rates as well as factors that affect remissions.Materials and Methods: We retrospectively investigated the results of 41 patients who were diagnosed with lupus nephritis after kidney biopsy in the Nephrology and Immunology-Rheumatology departments of Atatürk University Medical Faculty Training Hospital between January 2000 and December 2008. Demographic information, clinical history and laboratory results were collected from each patient’s records. The relationships among clinical, laboratory, demographic parameters and remissions were investigated. The patients were grouped in terms of urine protein levels; patients with urine protein < 330 mg/day were regarded as in remission and patients with urine protein ≥ 330 mg/day were were regarded as uncontrolled.Results: At the end of a 12-month period of therapy, 24 (58.5 %) of the patients were in remission. There were no statistically significant relationships among age, sex, anti-ds-DNA, C3, C4, activity indexes, chronicity indexes, serum level of creatinine, urine protein levels and remission (p>0.05). We compared class 3 LN patients at the 6th and 12th months according to treatment protocols. Azathioprin or mycophenolate mophetil were significantly better at placing urine protein levels in remission as compared to cyclophosphamide (p<0.05).Conclusion: According to our study, no relationship was found between basal clinical and laboratory parameters and patient remission. Response rates of our LN patients were similar to those in the literature. However, complete remission is still a problem in LN. The results of the protocols used in the treatment of LN show similarities. Although there are some data suggesting that MMF used in recent years is effective, it should be supported by prospective multicenter studies. It is important to note that it is difficult to achieve complete remission in LN patients.